2012
DOI: 10.1155/2012/126369
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus-Eluting versus Paclitaxel-Eluting Stents in Percutaneous Coronary Intervention: Meta-Analysis of Randomized Trials

Abstract: Background. Individual randomized trials have suggested that everolimus-eluting stents may have improved clinical outcomes compared to paclitaxel-eluting stents, but individual trials are underpowered to examine outcomes such as mortality and very late stent thrombosis. Methods. Medline, Cochrane, and conference proceedings were searched for randomized trials comparing everolimus versus paclitaxel-eluting stents for percutaneous coronary intervention. Results. 6792 patients were included from 4 randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…A comprehensive network meta-analysis by Palmerini T et al [25], in which 50,844 patients with unclassified coronary heart diseases were enrolled, showed that the second-generation DES, EES but not ZES, had the lower rate of stent thrombosis within 2 years of implantation than bare-metal stents and first-generation DES. The beneficial effect of EES was also confirmed by another small-scale meta-analysis performed by Alazzoni A et al [26]. However, another meta-analysis of 19 trials including 16,924 unrestricted coronary artery disease subjects did not find the differences in stent thrombosis between the overall second-generation DES and the overall first-generation those during the first year after stent implantation [27].…”
Section: Discussionmentioning
confidence: 74%
“…A comprehensive network meta-analysis by Palmerini T et al [25], in which 50,844 patients with unclassified coronary heart diseases were enrolled, showed that the second-generation DES, EES but not ZES, had the lower rate of stent thrombosis within 2 years of implantation than bare-metal stents and first-generation DES. The beneficial effect of EES was also confirmed by another small-scale meta-analysis performed by Alazzoni A et al [26]. However, another meta-analysis of 19 trials including 16,924 unrestricted coronary artery disease subjects did not find the differences in stent thrombosis between the overall second-generation DES and the overall first-generation those during the first year after stent implantation [27].…”
Section: Discussionmentioning
confidence: 74%
“…16 Binary restenosis rates at follow-up showed that patients who presented with anginal symptoms were significantly low in limus group than in the paclitaxel group which is similar to the studies conducted in the past. [17][18][19][20] No deaths or MI were reported at follow-up. Target lesion revascularization, target vessel revascularization, and target vessel failure rates were similar between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…EES have been found to be superior to PES [ 11 , 27 29 ] and comparable to SES [ 30 , 31 ] with respect to cardiac death, MI, stent thrombosis, and revascularization in randomized trials and prospective cohort studies of general populations. ZES have also been found to be superior to PES [ 15 , 32 ] and comparable to SES [ 32 , 33 ] with respect to death rate and MI in randomized trials of general populations.…”
Section: Discussionmentioning
confidence: 99%
“…Sirolimus-eluting and paclitaxel-eluting stents (SES and PES), hereafter referred to as first-generation DES, are superior to BMS with respect to the in-stent restenosis rate and target lesion revascularization after CTO PCI [ 7 10 ]. However, everolimus-eluting and zotarolimus-eluting stents (EES and ZES), hereafter referred to as second-generation DES, have been found to be superior or comparable to first-generation DES for composite outcomes in non-CTO lesions [ 11 15 ]. In the context of CTO, a few studies have compared the impacts of second-generation DES on clinical outcomes with those of first-generation DES.…”
Section: Introductionmentioning
confidence: 99%